Soil survey and land evaluation at Đông Cát and Bình Sơn 3 state farm, Việt Nam - Starisky, Igor (Wageningen Agricultural Univ, 1987)
This report describes the soil mapping of two farms in South Viet Nam. Two maps were made for each area, one with a scale of 1:44,000 using old 1954 Fremch airphoto's of the same scale. Secondly a more detailed soil survey was done on a part of each statefarm using a grid survey method. The detailed maps have a scale of 1:10,000. In the areas which were mapped in detail profile pits were dug and describled. Samples were taken to the VH-10 laboratory in Can Tho and analyzed to obtain data for a land evaluation